Special Effects and the Making of Pseudo-Monsters in Nollywood Zombie Films - Endong, Floribert Patrick C. (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2023)
Horror movies are artfully constructed to simultaneously elicit fear and thrill audiences. They essentially integrate gory, frightful and obscene creatures (notably the living dead, the undead, paranormal beings and aliens), as well as scary or terrifying scenes all designed to build the fear appeal or the fight-or-flight response. The mobilization of such scary scenes and creatures always entails the use of relevant, realistic – and professional-quality – costumes, make-up, special effects and editing among other technical tools. These tools are generally extremely exorbitant and not affordable to small-budget African filmmakers like the majority of Nigerian videastes who most often rely on very meager resources to produce their movies. In effect, the inability to lay hand on professional-quality make-up and special effects causes most Nigerian video filmmakers to rely on sub-standard tools which do not always actualize the aesthetic and fear appeal expected in a horror film. This scenario could well be illustrated using the way monsters and apocalyptic scenes are treated in most Nollywood zombie movies. In such movies, the leverage of sub-standard and grotesque make-up and special effects most often leads to the creation of pseudo-zombies which, instead of instilling fear and the fight-or-flight response, are susceptible to baffle or amuse film viewers and critics.